2022
DOI: 10.1007/s00167-022-07038-8
|View full text |Cite
|
Sign up to set email alerts
|

Arithmetic hip-knee-ankle angle and stressed hip-knee-ankle angle: equivalent methods for estimating constitutional lower limb alignment in kinematically aligned total knee arthroplasty

Abstract: Purpose Kinematically aligned total knee arthroplasty (KA TKA) relies on precise determination of constitutional alignment to set resection targets. The arithmetic hip-knee-ankle angle (aHKA) is a radiographic method to estimate constitutional alignment following onset of arthritis. Intraoperatively, constitutional alignment may also be approximated using navigation-based angular measurements of deformity correction, termed the stressed HKA (sHKA). This study aimed to investigate the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 55 publications
2
12
1
Order By: Relevance
“…The present findings are in accordance with previous studies demonstrating that either CPAK phenotypes I or II were the most commonly observed knee phenotypes in both healthy knees [12, 18, 21] and arthritic patients undergoing TKA [14, 18, 21, 31, 37, 40]. A recent study evaluating the CPAK phenotype distribution among 8739 osteoarthritic knees, identified CPAK phenotype I and II as the predominant phenotypes, with incidences of 28.1% and 27.3% respectively [14].…”
Section: Discussionsupporting
confidence: 94%
“…The present findings are in accordance with previous studies demonstrating that either CPAK phenotypes I or II were the most commonly observed knee phenotypes in both healthy knees [12, 18, 21] and arthritic patients undergoing TKA [14, 18, 21, 31, 37, 40]. A recent study evaluating the CPAK phenotype distribution among 8739 osteoarthritic knees, identified CPAK phenotype I and II as the predominant phenotypes, with incidences of 28.1% and 27.3% respectively [14].…”
Section: Discussionsupporting
confidence: 94%
“…The HKA angle is defined as the angle between the mechanical axes of the femur and tibia in the coronal plane 1 . Based on this angle, lower extremity alignment is classified as varus, neutral or valgus 2 4 . Many reports have shown that varus or valgus alignment increases the risk of incidence and progression of knee OA 5 9 .…”
Section: Introductionmentioning
confidence: 99%
“…this narrowing results in a fundamentally altered mhka, meaning estimation of the constitutional alignment is no longer possible using mechanical axis referencing. nevertheless, constitutional (or prearthritic) alignment can be approximated using the "arithmetic HKA" (aHKA = MPTA − LDFA), an especially useful tool when considering individualized surgical techniques, [13][14][15][16] provided the arthritic process has not yet caused significant bone wear.…”
mentioning
confidence: 99%